Detailing the epidemiological and clinical characteristics of chronic lymphocytic leukaemia in Portugal-Results from a population-based cancer registry cohort study. - Fábio Cardoso Borges (Public Library of Science (PLoS), 2021)
Background Chronic lymphocytic leukaemia (CLL) is the most common leukaemia among adults in western countries. Considering the increasing incidence and prevalence of this condition, it is highly relevant to better characterise these patients in Portugal, where data is still scarce. Methods To determine incidence, clinical presentation, survival and second malignancies, a population-based historical cohort study was conducted. Cases of interest were identified through the South Region Cancer Registry database and additional data sources. Patients aged ≥18 years, with a confirmed diagnosis of CLL or small lymphocytic lymphoma between January 1st, 2013 and December 31st, 2014 were included. Patients were followed-up until death or cut-off date (December 31st, 2019). Results A total of 496 patients were included and median follow-up time was 5.46 years. Crude incidence rates were 5.03 and 5.22 per 100,000 inhabitants for 2013 and 2014, respectively, and age-adjusted incidence rates were 3.18:100,000 European population for 2013 and 3.35:100,000 European population for 2014. Median age at diagnosis was 71 years and the male/female ratio was 1.40. The majority of patients had leukemic presentation of the disease (86.09%), was diagnosed in Binet stage A (75.58%) and did not present B symptoms (84.01%), anaemia (haemoglobin ≤10g/dL; 90.63%) nor thrombocytopenia (platelet count ≤100 000/μL; 91.73%). Five-year overall survival (OS) rate was 70.53% (95%CI 66.31-74.34) and age, lactate dehydrogenase, Binet stage and a ≥5 Charlson comorbidity index score were independently associated with OS. Standardised-incidence ratios for any second malignancy and cutaneous squamous cell carcinoma were 1.59 (95%CI 1.19-2.08) and 10.15 (95%CI 6.28-15.51), respectively. Conclusion Incidence, clinical presentation and survival of CLL Portuguese patients are similar to those reported for other western countries. The increased risk of second malignancies raises concerns and needs adequate clinical watchfulness.